Contested sacred ground and mistaken idioms: Pre -reducción and early reducción churches in South-central colonial Peru (AD 1536–1615) - Meddens, Frank M. (2025)
The cross followed the sword in the Spanish colonisation of the Americas. This Christian evangelisation went hand in hand with the conquistador’s subjugation of the Central Andeans. An evangelisation whose material correlates revolved around church architecture. In the colonial tumult of the first 80 years in the Andes, Christianity adapted swiftly to changing social and populational circumstances, and church buildings reflected this shift. We trace how church architecture, in the Andean highlands, changed and with it the deeper connotations of worship. A three to four phased evolution of churches, from open chapels, embedded churches, reducción churches and a final phase of add-ons such as belltowers, reflected how Andean society shifted from an animistic religion of space with churches linked to an Indigenous sacred landscape, to a Spanish Catholic religion of place focussed on the church building and internalised liturgical rituals. These changes mirrored deeper social transformations, as a fast-decreasing Indigenous population was concentrated in model colonial villages and towns (reducciones). These aimed at rooting out Prehispanic worship, and with it generate a more complete evangelisation of the local population. This severing of locals from their Prehispanic beliefs was a policy pushed by colonial and church authorities to control and convert.